Analisis Pengaruh Leadership Style Terhadap Kinerja Bisnis UMKM Melalui Networking Capability sebagai Variabel Mediasi - Rustianah Rustianah; Nining Yuningsih; Adi Maryadi (Universitas Islam Kadiri, 2023)
This study was conducted to provide empirical evidence regarding the effect of leadership style and on MSME business performance through networking capability as a mediating variable. This study used a sample of MSMEs located in Cicau Village, Central Cikarang. Sampling using Non Probability Sampling with a significance level used of 0.05 and analyzed using the PLS (Partial Least Square) application. Based on the results of the analysis, leadership style has a positive and significant effect on MSME business performance. The result of this study is that leadership style has a positive influence on innovation and business performance. Then the networking capability variable has a positive influence on MSME business performance. And networking capability mediates the influence between leadership style on MSME performance.